The Effectiveness of Social Stories Method with Audio Visual Media on Social Interaction and Positive Behavior in Children with Autism at the Bhakti Luhur Autism Therapy Unit Malang City Indonesia - Selvi Marce Pasapan; Ahsan Romadlon Junaidi; Ranti Novianti; Ediyanto Ediyanto (Jurnal ORTOPEDAGOGIA, 2025)
This research aims to analyze the effectiveness of social stories using audio-visual media on social interactions and positive behavior of children with autism. The research method used in this research is qualitative research with a literature study and observation approach. Children with Autism Spectrum Disorder experience difficulty in establishing social interactions with their environment. Based on the results of observations, the Bhakti Luhur Autism Therapist Unit, which is an early intervention therapy unit for children with autism, treated 38 children with Autism Spectrum Disorder specifications by dividing them into 6 groups according to ability. The results of observations carried out by teachers in group therapy class 1 consisting of 5 children with an average age of 7-11 years found that children had difficulty carrying out social interactions with the people around them, were less able to build reciprocal communication, and were unable to understand messages, difficulty in understanding unstructured social rules, difficulty in understanding and responding to other people's emotions, and not being able to imitate their environment so that they have difficulty interacting. By looking at the problems experienced by children with Autism Spectrum Disorder, it is necessary to use methods that can attract children's attention and social interaction skills through social stories. According to Sugiarto, et al (2004), quantitatively the treatment of social stories with picture cards is quite significant in improving the interaction abilities of children with Autism Spectrum Disorder. As technology develops, the presentation of social stories is basically less effective if it is only based on visuals. A more innovative approach is needed to overcome this. Isniawati, et al (2023) suggest adding activities related to social behavior through audio capture with more sophisticated tools.